Spatially Addressable Polarimetric Calibration of Reflective-Type Spatial Light Modulator Using Mueller–Stokes Polarimetry - Tiwari, Vipin; Pandey, Yukti; Bisht, Nandan S. (Frontiers in Physics, 2021)
Mueller-Stokes polarimetry is emerging as a prominent non-invasive imaging technique to study the structural characteristics of an anisotropic medium. Spatial light modulator (SLM) is a programmable liquid crystal device (LCD), which is used to modulate the amplitude, phase and polarization of light. The compact design and cumbrous manufacturing process of SLM requires its polarimetric calibration prior to its utilization for various applications. In this paper, we experimentally demonstrate Mueller-Stokes imaging of a reflective type SLM (Holoeye, LCR-720) to calibrate its polarization modulation characteristics with respect to its dynamic gray value range (0-255) at different spatial locations of SLM screen. Mueller matrices at 18 different gray values of SLM (at interval of 15) have been experimentally measured using an improvised Mueller Matrix Imaging Polarimeter (MMIP). Crucial polarimetric characteristics i.e. diattenuation, polarizance, State of Polarization (SOP), depolarization and retardance have been estimated with respect to the gray value range of SLM. A significant polarization modulation characteristics (diattenuation (0.08 to 0.3), polarizance (0.02 to 0.2), retardance (0 to π)) have been determined for the SLM. These results indicate that the SLM exhibits spatially variable depolarizing nature and hence it is not perfectly homogeneous in structure. Therefore, it is expected that the outcomes of this study would be helpful for exploring the applicability of Mueller-stokes polarimetry in advancement of LC technology.